Skills and knowledge as a basis for safety competence in teacher education curriculum - Brita Marianne Somerkoski (Finnish Social and Health Informatics Association, 2019)
Enhancing the safety culture in school context sets new challenges to prospective teachers, their need for safety skills, knowledge and competence. Based on the latest studies, the paper describes the factors of safety culture in the educational institutions. These factors are risks, processes, learning environments, learning, normative guidance, actors, target groups and tools. As a case study, further analysis is provided about the factor of learning. The data is teacher education curriculum text of one Finnish teacher education unit. In the content analysis, the data was first classified with themes in the context of safety. During the second round of analysis, special attention was paid to the verbs. Further, two groups, skills (S) and knowledge (K) were established. The analysis showed that there were more knowledge based (K) than skills based (S) meaning units. As the university studies are based on theoretical issues, this is understandable. Based on the analysis, it seems that the curriculum describes safety one-sided as the social issues and the interaction were in focus in both groups, knowledge and skills. This could mean that safety is valued in the teacher education. However, the results raise some concerns, whether the future teachers are able to provide decent education for their pupils in the various safety and security areas, such as traffic safety, injuries or occupational safety, or whether they are able to respond in the sudden crisis situations during the school day, for instance in case of violence or fire.